Side effects of sprays with azadirachtin mixed with Biolid E® against the natural parasitoids of Phyllocnistis citrella Stainton ( Lep. Gracillariidae ) (Bollettino di zoologia agraria e bachicoltura, 2024)
During Summer 1999 a tria! has been carried out in a citrus lemon orchard to testthe side effects of Azadirachtin (OIKOS®, 150ml/hl c.p.) mixed with mineral paraffinicoil (Biolid E®, 500 gr/hl) and a surfactant (AG.N.®, 50 gr/hl c.p.) respectively,against the natural parasitoids of the citrus leafminer (CLM). The statistica!analysis results should not indicate substantial differences between the totalpercentage of parasitism observed in the treated and untreated plants. Neverthelessduring the observations a percentage of 11,34 and of 16,67 of parasitoid larvaerespectively, some days after the first and the second spray, showed terathologicalsymptoms.
Keywords: Phyllocnistis citrella parasitoids; azadirachtin; terathological larval symptoms